Magnetism in crown-ether-substituted nitronyl nitroxide derivatives and their metal complexes - Sugano, T; Blundell, S; Hayes, W; Tajima, H; Mori, H (2012)
Rare-earth-metal (M = Nd, Gd and Dy) complexes of the organic monoradicals, 15-crown-5-phenyl nitronyl nitroxide 1 and 15-crown-5- or 18-crown-6-phenyl iminonitroxide 2, were synthesized. We present here magnetic properties of the metal-free radicals and the metal complexes of these organic monoradicals studied using SQUID megnetometry. Almost of all the rare-earth-metal complexes show two-sublattice behavior in a wide range of antiferromagnetic (AFM) intrasublattice and ferromagnetic (FM) intersublattice interactions, Γ and λ, with |CΓ | and |Cλ | ≅ 10 to 100 K (C is the Curie constant) over the temperature range between 1.8 and 300 K, while the metal-free radicals exhibit only weak AFM intermolecular interactions, less than the Weiss constant θ = -1 K. The magnitude of interactions observed in the metal complexes of each radical increase in order from Gd to Dy to Nd complexes. © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.